Assessment of farmer-oriented agricultural extension intervention in Iran. Issue 2 (15th March 2017) - Mohammadzadeh, Latif; Sadighi, Hassan; Abbasi, Enayat
ABSTRACT: Purpose : The main purpose of this study was to determine the characteristics of farmer-oriented policies as regards the Iranian agricultural extension system. Methodology : To fulfill this objective, a Delphi technique was utilized. The study used a series of three steps, engaging a panel of experts on farmer-oriented policies of agricultural extension system. Finding : The characteristics of farmer-oriented policies in agricultural extension system were classified into six categories including: need-based programs, proper interaction among stakeholders, decentralization and higher stakeholders' participation, enabling stakeholders with emphasis on smallholder farmers, market-oriented programs and integrated policies. The findings indicated that 'enabling farmers to solve their technical problems' and 'engaging farmers in planning, executing and evaluating of the programs' had the highest percentage of agreement. Theoretical implication : From a theoretical point of view, the finding of this research has introduced six categories as characteristics of a farmer-oriented policy that could have practical implications for agricultural extension system in Iran. Also, this paper proposes a framework for future studies in the field of farmer-oriented policies in agricultural extension system. Practical implications : Recognizing the characteristics of farmer-oriented intervention of agricultural extension shows that targeted extension approaches are needed to pay attention to these characteristics in various stages of planning, delivering and evaluation of extension programs. Originality/value : This paper provides a comprehensive list of characteristics of farmer-oriented policies of agricultural extension that can be helpful for agricultural policy-makers in devising programs of extension services.